The Beneficial Effects of a Multispecies Probiotic Supplement on Glycaemic Control and Metabolic Profile in Adults with Type 1 Diabetes: A Randomised, Double-Blinded, Placebo-Controlled Pilot-Study - Zhang X; Zhang Y; Luo L; Le Y; Li Y; Yuan F; Wu Y; Xu P (Diabetes, Metabolic Syndrome and Obesity, 2023)
Xiuzhen Zhang,* Ying Zhang,* Limei Luo, Ying Le, Ying Li, Fengyi Yuan, Yan Wu, Ping Xu Department of Endocrinology and Metabolism, Shenzhen People’s Hospital (The Second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology), Shenzhen, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ping Xu, Department of Endocrinology and Metabolism, Shenzhen People’s Hospital (The Second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology), Shenzhen, Guangdong, People’s Republic of China, Email xu.ping@szhospital.comObjective: In this pilot-study, the effects of a multispecies probiotic supplement on glycaemic control and metabolic parameters in adults with type 1 diabetes (T1DM) were explored.Material and Methods: A total of 50 T1DM patients were enrolled and randomly placed into a group receiving capsules containing multi-probiotic strains (Bifidobacterium longum, Lactobacterium bulagricumi, Streptococcus thermophilus) and insulin (probiotics group, n =  27) or a group receiving a placebo and insulin (placebo group, n = 23). All patients underwent continuous glucose monitoring at baseline and 12 weeks after intervention. The primary outcomes were determined by comparing factors such as changes in fasting blood glucose (FBG) and haemoglobin A1c (HbA1c) between the groups.Results: Probiotic supplementation significantly reduced FBG (− 1.0 ±  4.7 vs 1.8 ±  4.7 mmol/L, p = 0.048), 30 min postprandial glucose (− 0.5 ± 4.6 vs 1.9 ± 3.3 mmol/L, p = 0.0495), and low-density lipoprotein cholesterol (− 0.07 ± 0.45 vs 0.32 ±  0.78 mmol/L, p =  0.0413), compared with the placebo. Although not statistically significant, probiotic supplementation also lowered HbA1c levels by 0.49% (− 5.33 mmol/mol, p = 0.310). Besides, no significant difference was observed in the continuous glucose monitoring (CGM) parameters between the two groups. Further subgroup analysis revealed a significant reduction in mean sensor glucose (MSG; − 0.75 (− 2.11, 0.48) mmol/L vs 1.51 (− 0.37, 2.74) mmol/L, p = 0.010) and time above range (TAR; − 5.47 (− 20.1, 3.04)% vs 18.9 (− 1.11, 35.6)%, p =  0.006), as well as an greater improvement in the time in range (TIR; 9.32 (− 4.84, 16.6)% vs − 19.9 (− 31.4, 0.69)%, p =  0.005) in male patients than female patients in the probiotics group.Conclusion: Multispecies probiotics exerted beneficial effects on fasting and postprandial glucose and lipid profiles in adult T1DM patients, especially for male patients and those with higher baseline FBG levels.Keywords: continuous glucose monitoring, glycaemic variability, lipid profile, probiotics, type 1 diabetes mellitus